2021
DOI: 10.3390/su13073807
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of Spatiotemporal Variations in Temperature Extremes across China during 1960–2018

Abstract: Understanding the changing patterns of extreme temperatures is important for taking measures to reduce their associated negative impacts. Based on daily temperature data derived from 2272 meteorological stations in China, the spatiotemporal variations in temperature extremes were examined with respect to covariates by means of the Mann–Kendall test and a spatiotemporal model during 1960–2018. The results indicated that the temporal changes in cold extremes showed decreasing trends and warm extremes experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…are not applicable to this study. During the last several years, these 12 indices have been extensively deployed in the study of extreme temperatures around the world [9,[26][27][28]. The indices were calculated at each station using RClimDex 1.9 software (https://etccdi.pacificclimate.org/software.shtml, accessed on 10 November 2020).…”
Section: Definition Of Extreme Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…are not applicable to this study. During the last several years, these 12 indices have been extensively deployed in the study of extreme temperatures around the world [9,[26][27][28]. The indices were calculated at each station using RClimDex 1.9 software (https://etccdi.pacificclimate.org/software.shtml, accessed on 10 November 2020).…”
Section: Definition Of Extreme Temperaturementioning
confidence: 99%
“…IPCC (2021) also reported that climate change is already affecting natural and human systems across all continents and oceans as it has significant local and global impacts [5]. However, the spatial distribution of extreme temperatures is not the same worldwide, due to regional differences in climate system responses to enhanced radiative forcing and complex interactions between nonlinear climate systems and local and regional factors [4,9]. Numerous studies have shown that global extreme warm events of more than 70% have significantly increased, while extreme cold events have significantly decreased, including Australia [10], China [11], Europe [12], and North America [13].…”
Section: Introductionmentioning
confidence: 99%
“…It can be explained by increased concentrations of greenhouse gases and increased aerosols absorbed by nocturnal radiation [44]. It significantly affects the growth of vegetation [45][46][47]. Rising temperatures at night, for example, will increase plant respiration.…”
Section: Variation Characteristics Of Extreme Temperature Indices In Yunnan During 1960-2019mentioning
confidence: 99%
“…The Theil-Sen median method [104] is a robust non-parametric trend calculation method, which is not sensitive to measurement error and outlier data [18], and it has been widely used in the trend analysis of hydrologic time series [10,11,31,41,105]. It allows the data to have missing values and does not require the data to conform to a specific probability distribution [13].…”
Section: Theil-sen Median Methodsmentioning
confidence: 99%
“…Increased drying linked with higher temperatures and decreased precipitation has contributed to changes in drought [9]. Recent studies have documented that warming trends are expected to continue into the future [10,11]. Given this context, changes in spatial-temporal patterns of precipitation and temperatures are likely to make droughts more recurrent [12].…”
Section: Climate Change Characterized By Global Warming Has Become An...mentioning
confidence: 99%